Motivation to Speak Up of Students. Case Study: Three High Schools in District 7, Ho Chi Minh City - Thu, Hong Ngoc Anh; Dung, Tran Thao; Nghi, Tran Ngoc Bao; Dung, Mai Thi Thuy (VNU Journal of Science: Education Research, 2021)
One of the orientations of the Vietnam general curriculum 2018 is “to create a friendly environment and challenging situations in order to encourage students’ participation in learning activities” [1]. However, in Vietnam, the passiveness of students in classrooms are common whilst teachers are the main source of knowledge and students rarely speak up [2]. This article investigates the motivation to speak up in class of 347 students in two types of high schools: public school and private school in District 7, Ho Chi Minh City by using qualitative approach. The main purpose is to examine the reality, causes and motivation to speak up and propose feasible measures to improve this issue and aim for effective implementation of the general curriculum 2018.